2022
DOI: 10.1136/ejhpharm-2021-003172
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinical enquiries received by five COVID-19 vaccination centres in the UK

Abstract: The aim of this study was to explore the nature of clinical enquiries received by UK vaccination centres during the early stages in the roll-out of the COVID-19 vaccination programme. Four centres were situated in acute hospitals and one centre was in a designated public site. Data were collected for eight consecutive weeks between January and February 2021. The hospital centres administered a total of 28 995 doses of the Pfizer BioNTech vaccine, receiving 806 enquiries (1 enquiry per 36 vaccinations, 2.7%). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Currently, there are only limited studies examining COVID-19 vaccine administration errors. A previous study that analyzed clinical inquiries at five COVID-19 vaccination centers in London reported mainly on patient factors such as allergies, immunosuppression, and compatibility of vaccines with other medications [ 37 ]. In April 2021, the Institute for Safe Medication Practices (ISMP) indicated that 20% of COVID-19 vaccine errors reported were due to lower- or higher-than-authorized dosage [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are only limited studies examining COVID-19 vaccine administration errors. A previous study that analyzed clinical inquiries at five COVID-19 vaccination centers in London reported mainly on patient factors such as allergies, immunosuppression, and compatibility of vaccines with other medications [ 37 ]. In April 2021, the Institute for Safe Medication Practices (ISMP) indicated that 20% of COVID-19 vaccine errors reported were due to lower- or higher-than-authorized dosage [ 38 ].…”
Section: Discussionmentioning
confidence: 99%